Pengembangan Sistem Informasi Personalia Sekolah Tinggi Ilmu Komputer "MNO" Depok Berbasis Web Intranet - Thomas Afrizal (INFORMAL: Informatics Journal, 2016)
In the era of globalization this has much to do application of information technology in various fields. Now with increasingly sophisticated technology (hardware) such that the greater memory, faster processor, and hard disk capacity is greater and is followed by the development of software technology. software) is increasingly diverse as multimedia applications and others to make the needed information will be quickly met. But besides those two factors there are some important components that must be considered is the human (brain-ware) and the database (database). Use of the database is intended as a means of data storage or computerized information. It can reduce errors during the operation which is still done manually. Therefore, to support effective civil information systems need to be designed a database system more comprehensive staffing so that it will facilitate the processing of data - the data required. Based on the above scope, need to be seen as the existence of a database application to store all data in a controlled and relatively secure from viruses and other damage to both. This database whenever possible should be easily accessible by employees of high school computer science "MNO" which typically have permissions to display the data on applications based intranet is necessary server database, should also be able to interact or relate to software infrastructure of this campus so easy to implement. For writing PHP coding (For this application builder script), MySQL (a database server or storage of the data base), Apache (as a web server because these applications based intranet, or local). All this software can relate and interact with software infrastructure on this campus, sehigga easier for employees as users.